Beating the Impostor Syndrome - Mount, Portia; Tardanico, Susan (Center for Creative Leadership, 2014)
The Impostor Syndrome is a well-researched, well-documented phenomenon that occurs when successful and intelligent professionals feel they do not deserve their accomplishments and that they have faked their way to success. This syndrome can cause negative stress, fear, anxiety, loss of confidence, and can eventually lead to derailment. However, by overcoming inaccurate beliefs about yourself and your abilities, you can overcome the Impostor Syndrome and enjoy a more fulfilling career.